Implementing Brainwriting Strategy on Improving Writing Skills for English Intermediate Level Students - Vanesse Goh; Maya Marsevani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The aim of this study was to improve English intermediate level students in writing using brainwriting strategy. This is a Classroom Action Research which consists in total of seven meetings; two meetings for test and 5 meetings for treatment. The population of this research was the students who have joined English tuition on Intermediate level which consisted of 7 students. The steps of this research were (1) observing students’ difficulties in writing, (2) implementing brainwriting strategy and (3) writing practice using brainwriting strategy. The instruments of this research were observation and tests (pre-test and post-test). The results of this research are students able to improve their writing skills on fictional story and become more active in the classroom through brainwriting strategy which is shown by the average score of pre-test (1,95) with not enough category and post-test (2,42) with enough category